2015
DOI: 10.1111/ecin.12240
|View full text |Cite
|
Sign up to set email alerts
|

Firm Survival, Uncertainty, and Financial Frictions: Is There a Financial Uncertainty Accelerator?

Abstract: Using a large panel of unquoted UK firms over the period [2000][2001][2002][2003][2004][2005][2006][2007][2008][2009], we examine the impact of firm-specific uncertainty on corporate failures. In this context we also distinguish between firms which are likely to be more or less dependent on bank finance as well as public and nonpublic companies. Our results document a significant effect of uncertainty on firm survival. This link is found to be more potent during the recent financial crisis compared with tranqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 75 publications
(161 reference statements)
4
19
0
Order By: Relevance
“…Guariglia et al (2016) confirmed the earlier finding using UK data but for a different period; they maintained that an economic crisis tended to hit bank-dependent and non-exporting firms hard through higher interest rates. This channel of interest rates during a financial crisis was echoed by Boeri et al (2013), who stated that firms that have borrowed more experience larger layoffs, and by Byrne et al (2016), who emphasized that bank-dependent nonpublic firms end up with higher rates of failure due to increased uncertainty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Guariglia et al (2016) confirmed the earlier finding using UK data but for a different period; they maintained that an economic crisis tended to hit bank-dependent and non-exporting firms hard through higher interest rates. This channel of interest rates during a financial crisis was echoed by Boeri et al (2013), who stated that firms that have borrowed more experience larger layoffs, and by Byrne et al (2016), who emphasized that bank-dependent nonpublic firms end up with higher rates of failure due to increased uncertainty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The recent global economic crisis of 2008 involved a change in the socio‐political and economic environment that was of particular interest in terms of relocation processes (Domański et al, ; Pavlínek, ). This was mainly because the key element characterising the crisis was uncertainty, which conditioned the decisions that managers made (Byrne, Spaliara, & Tsoukas, ; Nelson & Katzenstein, ).…”
Section: Introductionmentioning
confidence: 99%
“…Bank‐dependent firms rely heavily on bank finance and have limited access to long‐term debt. As banks significantly cut credit to firms during the crisis, we expect that more bank‐dependent firms suffered more (see Santos, ; Byrne, Spaliara and Tsoukas, ). Similarly, smaller firms are associated with higher levels of information asymmetry (Spaliara, ).…”
Section: Empirical Specifications and Methodologymentioning
confidence: 99%